Ablation of ARNT/HIF1β in Liver Alters Gluconeogenesis, Lipogenic Gene Expression, and Serum Ketones - Wang, Xiaohui L. (2009)
We have previously shown that expression of the transcription factor ARNT/HIF1β is reduced in islets of humans with type 2 diabetes. We have now found that ARNT is also reduced in livers of diabetics. To study the functional effect of its reduction, we created mice with liver-specific ablation (L-ARNT KO) using ARNT loxP mice and adenoviral-mediated delivery of Cre. L-ARNT KO mice had normal blood glucose but increased fed insulin levels. These mice also exhibited features of type 2 diabetes with increased hepatic gluconeogenesis, increased lipogenic gene expression, and low serum β-hydroxybutyrate. These effects appear to be secondary to increased expression of CCAAT/enhancer-binding protein alpha (C/EBPα), farnesoid X receptor (FXR), and sterol response element-binding protein 1c (SREBP-1c) and a reduction in phosphorylation of AMPK without changes in the expression of enzymes in ketogenesis, fatty acid oxidation, or FGF21. These results demonstrate that a deficiency of ARNT action in the liver, coupled with that in β cells, could contribute to the metabolic phenotype of human type 2 diabetes.